Spectral emittance of ceramics for high temperature solar receivers. (1st July 2021) - Azzali, N.; Meucci, M.; Di Rosa, D.; Mercatelli, L.; Silvestroni, L.; Sciti, D.; Sani, E.
Highlights: Spectral normal emittance of SiC, TaB2 and ZrB2 ceramics is measured up to 850 °C temperature. Surface features of samples affect the temperature–dependent emittance. The size of surface features is key parameter. Borides show a thermal emittance significantly lower than silicon carbide. Abstract: In this work, for the first time, we studied the temperature-dependent spectral emittance of highly refractory ceramics, e.g. silicon carbide (SiC) and two ultra-high temperature ceramics (tantalum diboride (TaB2 ), zirconium diboride (ZrB2 )) to evaluate their potential for solar tower receivers applications. We measured the spectral normal emittance from 1 µm to 21 µm at temperatures up to 850 °C, in vacuum, by means of a novel experimental setup composed by an electric furnace connected to a FT-IR spectrometer. Comparison with previously published data collected with a different setup was also carried out to validate the results. In addition, the experimental spectral emittance was also compared with the values calculated from hemispherical reflectance at room temperature by means of Kirchhoff's law. The results show that surface features play a fundamental role in the emittance of investigated ceramics.